Pengaruh Sumber Daya Manusia, Teknologi Informasi dan Pengendalian Intern terhadap Kualitas Laporan Keuangan - yudianta, i gede agus (E-Jurnal Akuntansi; Vol 1 No 1 (2012), 2012)
Government agencies at this time, must keep track of accounting development  in order to create accountability and transparency. One of its efforts is the delivery of the qualified government financial statements. The purpose of this study was to determine the effect of human resource capacity, the utilization of information technology and accounting internal control to the quality of accounting information in SKPD Gianyar regency financial reporting. The used sampling method  is the saturated samples. Based on the analysis results, obtained that the capacity of human resources, the utilization of information technology and accounting internal control have a positive effect to the quality of accounting information in SKPD Gianyar regency financial reporting.
Keywords: human resources, information technology, internal control, information quality